The Effect of Gamification in HRIS Applications on Millennial Employee Performance and Engagement - Sri Hartono; Haziq Idris (Yayasan Adra Karima Hubbi, 2025)
Background. The development of information technology has encouraged organizations to digitize their HR management systems through the Human Resource Information System (HRIS). The millennial generation as the dominant users of this system demand an interactive and meaningful work experience, so the concept of gamification is starting to be applied in HRIS features to improve their participation and performance. Purpose. This study aims to analyze the influence of gamification in HRIS applications on the performance and work engagement of millennial generation employees, as well as examine the role of work involvement as a mediator in these relationships. Method. This study uses a quantitative approach with a correlational design. The sample consisted of 120 millennial employees at tech companies who used HRIS with gamification features. Data were collected through questionnaires and analyzed using multiple regression techniques and mediation tests. Results. The results show that positive perceptions of gamification have a significant effect on employee engagement and performance. Work engagement has been shown to be a partial mediator in the relationship between gamification and work performance. Conclusion. Gamification in HRIS has proven to be an effective strategy to increase the motivation and productivity of millennial employees. An engaging, competitive, and interactive work system makes a positive contribution to a more meaningful work experience.